Trapped in the COVID-19 pandemic: The effect of risk concern and emotions on burnout among health care workers - Sousa, I. C.; Almeida, T.; Correia Leal, C. (Psicologia, 2021)
The COVID-19 pandemic poses critical challenges for the health care workers (HCWs) around the world due to the increasing demands imposed on health care systems. This study aims to investigate how risk concern impacts burnout via positive and negative affect. Further, the moderating role of risk exposure (low, medium, and high) in this parallel mediation model is examined. A sample of 257 Portuguese HCWs answered a questionnaire. Structural equation modeling (SEM) analysis was applied. Results showed that risk concern positively influences negative affect – but not positive affect – and, consequently, burnout. Contrary to our expectations, this indirect effect was not greater for individuals in the high-risk group (vs. low-risk group), which can be explained by individual and organizational factors' buffering role. These findings draw healthcare organizations' attention to the hazardous effects of risk concern on HCWs' well-being.